2020
DOI: 10.1002/jcb.29663
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐1 facilitates hypoxia‐induced injury by targeting NOTCH3

Abstract: Cell proliferation, apoptosis, and autophagy have been reported to be related to myocardial ischemia injury. MicroRNAs have attracted wide attention on regulating cell proliferation, apoptosis, and autophagy. miR‐1 expression has been reported to be dysregulated in cardiac tissue or cells with hypoxia, while the exact roles as well as underlying mechanism remain poorly understood. In this study, we investigated the potential roles of miR‐1 in cell proliferation, apoptosis, and autophagy in hypoxia‐treated card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The relationship between aggregation and cellular toxicity remains controversial, and the uncoupling of aggregation and toxicity is observed in various disease models. Mammalian studies suggest context-dependent mir-1 effects, where mir-1 either promotes or inhibits autophagy ( Ejlerskov et al, 2020 ; Hua et al, 2018 ; Xu et al, 2020 ). Whether miR-1 is proteoprotective or limits proteoprotection in C. elegans could hinge on many factors.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between aggregation and cellular toxicity remains controversial, and the uncoupling of aggregation and toxicity is observed in various disease models. Mammalian studies suggest context-dependent mir-1 effects, where mir-1 either promotes or inhibits autophagy ( Ejlerskov et al, 2020 ; Hua et al, 2018 ; Xu et al, 2020 ). Whether miR-1 is proteoprotective or limits proteoprotection in C. elegans could hinge on many factors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that miRNAs can negatively regulate gene expression via the translational suppression of target mRNAs, playing critical roles in regulating cell proliferation, apoptosis and autophagy ( 46 , 47 ). Various disease-specific miRNAs, such as miR-155, miR-194 and miR-182 have been identified to exert their biological functions in renal tubular epithelial cells subjected to H/R via suppressing their downstream molecules ( 20 , 24 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three miRNAs are interesting-miR-1, miR-155 and miR-204. These miRNAs are connected with proliferation, apoptosis, and cardiac injury [25] as well as transforming growth factor-β1 (TGF-β1) and glial cell line-derived neurotrophic factor (GDNF) regulation during glaucoma, asthma and obesity [26][27][28][29]. However, what is even more interesting is that it has been also shown that these miRNAs regulate brain-derived neurotrophic factor (BDNF) [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The level of this miRNA was lower in the serum of control groups of NET-KO and SWR/J, and it decreased in WT mice upon RS, while it did not change in other two genotypes. The miR-1 has been associated with cardiac dysfunction, immunology (allergy), skeletal muscle changes (amyotrophic lateral sclerosis), but also as a regulator of glucose metabolism in the liver [25,[43][44][45]. It was also detected during stress studies, such as temperature changes, exercise (longer running), and stress connected with elevated platforms [38,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%